Síntese do Mo2C e NiC em reator de leito fixo suportados em carvão ativado por impregnação expressa - Nóbrega, Fábio André Moura (2024)
The circular economy has been used as one of the main solutions for reducing environmental impacts. The reuse of waste produced in the most varied industrial activities can occur in several ways, one of which can be through hydrotreatment reactions (HDT) which are catalyzed by solids. In this context, the objective of this work is to synthesize catalysts capable of hydrogenating carbohydrates or hydrocarbons. Examples include: the hydrogenation of Lactose, present in whey, a residue from cheese manufacturing, into Lactitol and the hydrogenation of glycerol, present in biodiesel, a residue from its manufacture, into propylene glycol. An express method for supporting catalysts was proposed, replacing the analytical one. The precursor to obtain [Mo2C] was [(NH4)6[Mo7O24].4H2O], and to obtain [NiC] two precursors were used: [Ni(NO3)2.6H2O] and [NiCl2.6H2O ]. The precursors were characterized by TG/DTA, SEM/EDS and XRD. The carbides were obtained through a gas-solid reaction with an atmosphere of methane (CH4) and hydrogen (H2) using a fixed bed reactor. A total gas mixture flow rate of 20L/h was used with 5% CH4 and a heating rate of 10°C/min, up to the reaction temperature (500o to 800°C). The reaction products were characterized by XRD, SEM/EDS and BET. The presence of a Mo2C phase was found in the carburization at 700°C (orthorhombic) and 750ºC (hexagonal) in a 1h isotherm. The identification of the phase containing NiC (cubic) by the diffractograms was detected through a gas-solid reaction with an atmosphere of methane (CH4) and hydrogen (H2) at a temperature of 500°C in the presence of CAP and at 800°C in a 3h isotherm. BET analysis for Mo2C and Mo, both supported on CAP, indicated a surface area of 69 m2 /g and 349 m2 /g, respectively. The synthesis of transition metal carbides, such as (Mo2C) and (NiC), has attracted great interest due to their unique catalytic properties. These materials have potential for diverse industrial applications, including methane reforming, fuel cells, hydrogenation and dehydrogenation reactions. The search for efficient and sustainable methods for producing these catalysts is an active field of research in chemical engineering. The NiC synthesis methodology is an innovation in scientific literature.